Characterization Method of the Damping in Harmonically Forced Two-State Piecewise Linear Elastic Structures - ALZUBAIDI, Bilal; NÉMETH, Róbert K. (Computer Assisted Methods in Engineering and Science, 2025)
An equivalent viscous damping ratio is introduced to characterize the energy dissipation caused by the plastic impact in the periodic responses of piecewise linear elastic systems.